Pelatihan Pengembangan Pendidikan Karakter bagi Siswa MTs Nurul Huda Mendalo Darat – Jambi Luar Kota - Latusi Anggriani; Fitri Ana Siregar; Zakiyatunnisa Al Mubarokah; Urwawuska Ladini; Saldi Yulistian; Nurfazillah Nurfazillah; Miftahur Rahmi (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
Madrasah plays an important role as a place to pass on the values of ahl al-sunnah wa al-jama'ah. Madrasah has the same status as general educational institutions and has the characteristics of the Islamic religion. The increasing phenomenon of juvenile delinquency and the declining quality of student character, strengthening the function of education as a character builder has re-emerged and become an urgent and inevitable demand. The purpose of this community service is to launch a national character education movement starting from early childhood education to college. This launch is expected to overcome the problem of low student character. The method used in community service activities with systematic, structured, measurable stages, and real results of the activities carried out, namely observation, orientation, introduction of materials, implementation, and evaluation. The results of community service, character education is important to be given to students because the formation of a child's character is obtained in the school environment. This service has a positive impact on students of MtS Nurul Huda Mendalo because students are able to understand the importance of Character Education being applied in social life. Students are able to provide examples of the application of Character Education after the material for developing Character Education is given. Through this activity, students can learn that character education is not only provided at the MtS level, but is provided up to the tertiary education level.